PERSEPSI LANSIA TENTANG DUKUNGAN KELUARGA TERHADAP KEPATUHAN DIET HIPERTENSI - Lia Hikmatul Maula; Mariah Ulfah; Ita Apriliyani (Bina Generasi : Jurnal Kesehatan, 2023)
Hypertension and its complications can be overcome and prevented through a healthy lifestyle. One of them is a healthy lifestyle for people with hypertension, namely diet compliance. The family plays an important role in the management of hypertension, because it can increase the confidence and motivatiob of the elderly in a adherence to the hypertension diet. The purpose of this study is to determine the perception of the elderly about family support for hypertension diet compliance. The research uses a quantitative analytical observational method with a cross-sectional design. The sample of this research used purposive sampling technique. The participant of this study were 69 respondents who met certain criteria. Data were taken by filling out questionnaires on family support and hypertension diet compliance. Data analysis using chi-square test. The results showed that the majority of hypertension respondents aged 55-65 years (71.0%), female (65.2%), elementary school education(56.5%), unemployed as much (55.1%) and had received information about hypertension diet as much as (65.2%). The elderly’s perception of family support is in a good category (58.0%) and the level of adherence to the hypertension diet is in the obedient category (82.6%). The results of the bivariate analysis obtained a p-value of 0.011, which means Ha is accepted. So it can be concluded that there is a relationship between the elderly’s perception of family support for hypertension diet compliance.